Changes in the Spatial Distribution of Elementary Schools and Their Impact on Rural Communities in Czechia in the Second Half of the 20th Century - Silvie Kucerova; Zdenek Kucera (Journal of Research in Rural Education, 2012)
This article addresses the changes in the spatial distribution of elementary schools in Czechia in the second half of the 20th century and the consequences of these changes on the functioning of rural communities. The spatial distribution of elementary schools, the shape of their catchment areas, and the regional and local communities connected with these schools are influenced by a wide variety of general processes similar to those in the majority of developed countries. We find decreases in the number of elementary schools, along with a concentration of elementary education provisions, in larger population centers. In Czechia the primary phase of this process occurred during the 1970s as a result of the implementation of a unique totalitarian policy of centrally directed settlement development. The effects of school closure on rural communities in peripheral areas fail to show any fundamental difference between Czechia and other developed countries, although the unique features of the former communist system are expressed in the time and forms of school closures and the resulting spatial patterns of school distribution.